THE EFFECT OF JOB SATISFACTION ON EMPLOYEE PERFORMANCE THROUGH ORGANIZATIONAL CITIZENSHIP BEHAVIOR: A STUDY AT PERUMDA TIRTANADI HEAD OFFICE OF NORTH SUMATRA - Nia Luthfiana Marina; Prihatin Lumbanraja; Meilita Tryana Sembiring (RADJA PUBLIKA, 2025)
This study examines the influence of job satisfaction on employee performance, with Organizational Citizenship Behavior (OCB) as a mediating variable, in Perusahaan Umum Daerah (Perumda) Tirtanadi, North Sumatra. Using a quantitative approach, data were collected from 100 employees selected through purposive sampling. The data were analyzed using path analysis with the SmartPLS application. The results reveal that job satisfaction has a significant positive effect on OCB (path coefficient β = 0.627; p < 0.001) and on employee performance (β = 0.360; p < 0.01). Furthermore, OCB significantly influences employee performance (β = 0.479; p < 0.001). The indirect effect of job satisfaction on performance through OCB (β = 0.300) is greater than the direct effect, confirming OCB’s role as a mediating variable. This suggests that employees who are more satisfied with their jobs are more likely to exhibit positive voluntary behaviors that contribute to higher performance levels. The findings align with Social Exchange Theory, which posits that positive treatment by the organization encourages employees to reciprocate with constructive behaviors. Herzberg’s Two-Factor Theory also supports the view that both hygiene and motivational factors influence satisfaction, which in turn fosters improved work outcomes. This study highlights the strategic importance of enhancing job satisfaction and promoting OCB to improve performance in public service organizations. Future research should consider incorporating moderating variables such as leadership style, organizational commitment, or work culture, and employing longitudinal designs to validate the causal pathways.